Compensatory network changes in the dentate gyrus restore long-term potentiation following ablation of neurogenesis in young-adult mice - Singer, Benjamin H. (National Academy of Sciences, 2011)
It is now well established that neurogenesis in the rodent subgranular zone of the hippocampal dentate gyrus continues throughout adulthood. Neuroblasts born in the dentate subgranular zone migrate into the granule cell layer, where they differentiate into neurons known as dentate granule cells. Suppression of neurogenesis by irradiation or genetic ablation has been shown to disrupt synaptic plasticity in the dentate gyrus and impair some forms of hippocampus-dependent learning and memory. Using a recently developed transgenic mouse model for suppressing neurogenesis, we sought to determine the long-term impact of ablating neurogenesis on synaptic plasticity in young-adult mice. Consistent with previous reports, we found that ablation of neurogenesis resulted in significant deficits in dentate gyrus long-term potentiation (LTP) when examined at a time proximal to the ablation. However, the observed deficits in LTP were not permanent. LTP in the dentate gyrus was restored within 6 wk and this recovery occurred in the complete absence of neurogenesis. The recovery in LTP was accompanied by prominent changes within the dentate gyrus, including an increase in the survival rate of newborn cells that were proliferating just before the ablation and a reduction in inhibitory input to the granule cells of the dentate gyrus. These findings suggest that prolonged suppression of neurogenesis in young-adult mice results in wide-ranging compensatory changes in the structure and dynamics of the dentate gyrus that function to restore plasticity.